THE MONTHLY CHANGING OF THE LOWEST POPULATION DENGUE VIRUS INFECTION IN PATIENT AT SOERYA HOSPITAL SIDOARJO IN 00 - Soegijanto, Soegeng (Indonesian Journal of Tropical and Infectious Disease, 2011)
Background: Dengue virus infection is one of the important health problems in Indonesia, although the mortality rate has been decreased but many dengue shock syndrome cases is very difficult to be solving handled. To solve this problem, some factor that influence the prevalence of dengue virus infection should be studied. The Aim of Study: To detect some factor that maintain the higher case of dengue virus infection in patient at the Soerya Hospital Sepanjang, Sidoarjo. Material & Method: Study had been done at Soerya Hospital Sepanjang, Sidoarjo since January 1, 2007 until December 31, 2010. All cases suspected dengue virus infection in patient at soerya hospital were diagnosed based on WHO criteria in 1997 and PCR examination in ITD laboratory. The Result: In 2007, 2008, 2009, the monthly observation showed that decreasing cases of dengue virus infection in patient at Soerya Hospital had been found on September, but in 2010 this event had been found on November. Why this event to be change? It is suggested might be due to global warming in the world and the climate going to influence the environment sanitation. Interaction between agent host and environment becoming increase it might be due to the changing of climate can influence the growing population Aedes Aegyptie and Aedes Albopictus promoting to increase vector for transmit dengue virus infection. It is prominent in sub urban area, with have many peoples donât aware with the bad environment sanitation. And many peoples showed very dynamic for living until the idea good environment do not be thought. By this condition the monthly population dengue virus infection in patient at hospital are going to maintain higher more than six months than usually. On the year 2007, 2008, 2009 the lowest cases found on September. In 2010, the lowest cases had been found on November. The Conclusion: Global warming, increasing sub urban area which have many peoples donât aware with the bad environment sanitation and have highly dynamic peoples for getting some money for their life, could influence the higher cases dengue virus infection in patient at hospital more than 6 months.